2007
DOI: 10.1162/evco.2007.15.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Speeding Up Evolutionary Algorithms through Asymmetric Mutation Operators

Abstract: Successful applications of evolutionary algorithms show that certain variation operators can lead to good solutions much faster than other ones. We examine this behavior observed in practice from a theoretical point of view and investigate the effect of an asymmetric mutation operator in evolutionary algorithms with respect to the runtime behavior. Considering the Eulerian cycle problem we present runtime bounds for evolutionary algorithms using an asymmetric operator which are much smaller than the best upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Moreover, our runtime bound is a √ m-factor slower than Papadimitriou-McDiarmid for reasons we discuss at the end of the section. Nevertheless, we consider these modifications in the context of tailored search operators [6,14,22]. Specifically, we want to show that even small modifications that incorporate problem-specific knowledge into the representation and variation operators can close a superpolynomial runtime gap.…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our runtime bound is a √ m-factor slower than Papadimitriou-McDiarmid for reasons we discuss at the end of the section. Nevertheless, we consider these modifications in the context of tailored search operators [6,14,22]. Specifically, we want to show that even small modifications that incorporate problem-specific knowledge into the representation and variation operators can close a superpolynomial runtime gap.…”
Section: Lemmamentioning
confidence: 99%
“…This is common in applications, but has also been studied from a theoretical perspective. Doerr et al [6] proved that tailored mutation operators for the Eulerian cycle problem on a graph of m edges can improve the efficiency of randomized local search and the (1 + 1) EA resulting in an upper bound of O(m 3 ). This beats the upper bound for the general version of the (1 + 1) EA by a factor of m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of (1+1) EAs on plateaus of different structures has been studied in [10] by a rigorous runtime analysis. In the case of combinatorial optimization problems, it has been shown that evolutionary algorithms have to cope with plateaus of constant fitness for the Eulerian cycle problem [2,13] and the computation of maximum matchings [6].…”
Section: Constant Population Sizementioning
confidence: 99%
“…In general, the use of modified op-erators in the evolutionary algorithms [5][6][7] allows having a reduction in the computational time, without losing complexity in the model of the problem to solve. However, the modification of the operators must be realized in every strategy, which requires profound knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%